2019
DOI: 10.7126/cumudj.497099
|View full text |Cite
|
Sign up to set email alerts
|

Post Herpetic Osteonecrosis of the Maxilla

Abstract: Herpes Zoster (HZ) is caused by the secondary reactivation of Varicella Zoster virus. It is characterised by presence of severe pain and unilateral vesicles along the distribution of the affected nerve. Osteonecrosis is one of the rare complications of Herpes Zoster which is seen after the acute phase of the illness has subsided. We report a case of osteonecrosis of the maxilla in 35-years-old female. The subject gave a history of Herpes Zoster of the maxillary branch of the trigeminal nerve. After healing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Ajila et al reported a 35-years-old female who presented with post-herpetic osteonecrosis of the maxilla, which led to the diagnosis of HIV infection. Such cases emphasize the importance of identification of retro-positive status at the earliest, since there is an ever increasing number of HIV-positive patients in the population who are susceptible to various types of infections, which in turn can help us in instituting effective treatment without a delay [11].…”
Section: Discussionmentioning
confidence: 99%
“…Ajila et al reported a 35-years-old female who presented with post-herpetic osteonecrosis of the maxilla, which led to the diagnosis of HIV infection. Such cases emphasize the importance of identification of retro-positive status at the earliest, since there is an ever increasing number of HIV-positive patients in the population who are susceptible to various types of infections, which in turn can help us in instituting effective treatment without a delay [11].…”
Section: Discussionmentioning
confidence: 99%